Anti-Tobacco Advertising—Is Bladder Cancer Adequately Addressed?. Issue 4 (4th July 2021) - Ferenczi, Basil; Lee, Wai; Frankel, Jason; Porter, Christopher; Corman, John
Abstract: Introduction: In order to assess whether bladder cancer is appropriately referenced in online anti-tobacco advertisements, we evaluated 200 videos and assessed diseases mentioned in these videos. This was then compared to relative incidence of tobacco-associated malignancy. Methods: Smoking cessation campaign videos were identified using the Google Video search page. The first 50 video results of 4 colloquial search terms were assessed for diseases mentioned. Videos were categorized as malignancy-related anti-tobacco advertisement or all anti-tobacco advertisement. Relative weight for each tobacco-associated malignancy was defined as the rate of reference within malignancy-related anti-tobacco advertisements divided by the incidence of that cancer among all smoking-related malignancies. Results: In all, 200 total videos were reviewed. The most common conditions highlighted were addiction (56, 27.0%) and death (26, 13.0%). The most common malignancies addressed were lung cancer (22, 11.0%), throat cancer (20, 10.0%) and oral cancer (9, 4.5%). Only 1 (0.5%) video mentioned bladder cancer. The relative weights of each malignancy were: lung cancer 1.09, oral cancer 18.26, throat cancer 1.94, bladder cancer 0.14. Conclusions: This study demonstrates the significant opportunity that exists for public education regarding the relationship between tobacco use and bladder cancer. Despite a relatively high incidence amongst tobacco-associated malignancies, bladder cancer is very poorly represented in anti-tobacco advertising with a relative weight of 0.14. It is possible that a more representative presentation of the adverse effects of tobacco use would be more efficacious in promoting tobacco cessation.